Lake Pavin History, geology, biogeochemistry, and sedimentology of a deep meromictic maar lake - Sime-Ngando, Télesphore; Boivin, Pierre; Chapron, Emmanuel; Jezequel, Didier; Meybeck, Michel (Springer International Publishing : Imprint: Springer, 2016)
This book represents the first multidisciplinary scientific work on a deep volcanic maar lake in comparison with other similar temperate lakes. The syntheses of the main characteristics of Lake Pavin are, for the first time, set in a firmer footing comparative approach, encompassing regional, national, European and international aquatic science contexts. It is a unique lake because of its permanently anoxic monimolimnion, and furthermore, because of its small surface area, its substantially low human influence, and by the fact that it does not have a river inflow. The book reflects the scientific research done on the general limnology, history, origin, volcanology and geological environment as well as on the geochemistry and biogeochemical cycles. Other chapters focus on the biology and microbial ecology whereas the sedimentology and paleolimnology are also given attention. This volume will be of special interest to researchers and advanced students, primarily in the fields of limnology, biogeochemistry, and aquatic ecology.